Enhancement of Clostridium butyricum hydrogen production by iron and nickel nanoparticles: Effects on hydA expression - Moura, A. G.L.; Rabelo, C. A.B.S.; Okino, C. H.; Maintinguer, S. I. [UNESP]; Silva, E. L.; Varesche, M. B.A. (Elsevier, 2020)
In this study, an optimized medium for Clostridium butyricum (CCT7470) was obtained from a Plackett-Burman assay. It was evidenced that glucose (5 g/L), starch (1 g/L) and three nitrogen and vitamin sources (5 g meat extract/L; 5 g peptone/L and 1.5 g yeast extract/L) improved hydrogen (H2) production. The addition of nanoparticles (NPs) improved the fermentation process, and maximum H2 production (434 ± 13 mL) was achieved with 30 mg Fe0/L and 20 mg Ni0/L. The metabolic pathway shifted from acetic and butyric to valeric acid production with the addition of NPs. In reactors with NPs, a longer permanence of hydrogenase was observed with hydA quantification by real-time polymerase chain reaction (qPCR). However, the expression of new enzymes, assessed by reverse transcription followed by qPCR (RT-qPCR), was higher in control assay than that in the NPs one.
Keywords: Clostridium butyricum; Dark fermentation; Iron nanoparticles; Nickel nanoparticles; Response surface methodology